TINJAUAN PELAKSANAAN PENGENAAN PAJAK PERTAMBAHAN NILAI PADA PT GRANDMININDO ANUGERAH - Ardyansari, Desy; Tobing, Josephine (Buletin Ekonomi, 2017)
One that uses tax collection system that is self-assessment is VAT. The legal basis for VAT is set in the Law of the Republic of Indonesia Number 8 Year 1983 on Value Added Tax And Or PPnBM as amended by Act No. 42 of 2009. The VAT is an indirect tax on consumption in the customs area means that the tax burden can be transferred to another party, as long as the assignor of the tax qualifies as a Taxable Entrepreneur (PKP). The purpose of this report is to know the activities of tax imposition on Lead Mining. The company is engaged in vessel rental services are subject to VAT on services. Field Work Practice (PKL) is performed to determine the implementation of the tax in court by comparing the theoretical basis obtained in the course. This activity was conducted from February to April 2016. During the performance PKL obtain accurate data on VAT by taking the data that the form of the Notice (SPT), Tax Payment (SSP). This report can be concluded that PT Anugerah Grandminindo has run tax obligations in accordance with the Law of the Republic of Indonesia Number 8 Year 1983 on Value Added Tax And Or PPnBM as amended by Act No. 42 of 2009. It can be seen from the already implementation of the obligations that levy VAT at 10% of rental services vessels transferred to the recipient of services, publishes a Tax Invoice as proof of collection of VAT and SSP as proof of deposit and filing (SPT) Masa PPN done before the deadline for submission of return period expires namely the 20th of the following month.Keywords : Tax Payment (SSP), Value Added Tax